Α7 Nicotinic Receptor Promotes the Neuroprotective Functions of Astrocytes against Oxaliplatin Neurotoxicity. (3rd June 2015) - Di Cesare Mannelli, Lorenzo; Tenci, Barbara; Zanardelli, Matteo; Failli, Paola; Ghelardini, Carla
Abstract : Neuropathies are characterized by a complex response of the central nervous system to injuries. Glial cells are recruited to maintain neuronal homeostasis but dysregulated activation leads to pain signaling amplification and reduces the glial neuroprotective power. Recently, we highlighted the property of α 7 nicotinic-acetylcholine-receptor (nAChR) agonists to relieve pain and induce neuroprotection simultaneously with a strong increase in astrocyte density. Aimed to study the role of α 7 nAChR in the neuron-glia cross-talk, we treated primary rat neurons and astrocytes with the neurotoxic anticancer drug oxaliplatin evaluating the effect of the α 7 nAChR agonist PNU-282987 (PNU). Oxaliplatin (1  μ M, 48 h) reduced cell viability and increased caspase-3 activity of neuron monocultures without damaging astrocytes. In cocultures, astrocytes were not able to protect neurons by oxaliplatin even if glial cell metabolism was stimulated (pyruvate increase). On the contrary, the coculture incubation with 10  μ M PNU improved neuron viability and inhibited apoptosis. In the absence of astrocytes, the protection disappeared. Furthermore, PNU promoted the release of the anti-inflammatory cytokine TGF- β 1 and the expression of the glutamate-detoxifying enzyme glutamine synthetase. The α 7 nAChR stimulation protects neurons from oxaliplatin toxicity through an astrocyte-mediated mechanism. α 7 nAChR is suggested for recovering the homeostatic role of astrocytes.